A Conceptual Model of Tactile Processing across Body Features of Size, Shape, Side, and Spatial Location - Tamè, Luigi; Azañón, Elena; Longo, Matthew R. (Frontiers in Psychology, 2019)
The processing of touch depends of multiple factors, such as the properties of the skin and type of receptors stimulated, as well as features related to the actual configuration and shape of the body itself. A large body of research has focused on the effect that the nature of the stimuli has on tactile processing. Less research, however, has focused on features beyond the nature of the touch. In this review, we focus on some features related to the body that have been investigated for less time and in a more fragmented way. These include the symmetrical quality of the two sides of the body, the postural configuration of the body, as well as the size and shape of different body parts. We will describe what we consider three key aspects: (a) how and at which stages tactile information is integrated between different parts and sides of the body; (b) how tactile signals are integrated with online and stored postural configurations of the body, regarded as priors; (c) and how tactile signals are integrated with representations of body size and shape. Here, we describe how these different body dimensions affect integration of tactile information as well as guide motor behaviour by integrating them in a single model of tactile processing. We review a wide range of neuropsychological, neuroimaging and neurophysiological data and suggest a revised model of tactile integration on the basis of the one proposed previously by Longo and colleagues (2010).